DINAMIKA IDENTITAS GENDER PADA ANAK-ANAK DI ERA DIGITAL - Pirdaus, Doni (Harakat an-Nisa: Jurnal Studi Gender dan Anak, 2022)
Gender identity is an important aspect of children's self-development that is influenced by various factors, including the social environment and digital technology. This study aims to explore the influence of digital media on the formation of gender identity in children in the digital era through a literature study method. The study analyzes a variety of relevant literature sources, including books, scientific journals, and academic articles, to identify key themes and gaps in the existing literature. The focus of the research includes the influence of social media, digital games, educational content, and the dynamics of online interaction on children's perception and expression of gender identity. The results show that digital media has a complex role in the formation of gender identity, both positively and negatively, depending on how the media is used and accompanied. The implications of these findings underscore the need for a more inclusive and critical approach to designing and supervising digital content consumed by children. The study also identified several limitations, including limitations in the scope of literature that may not fully represent all aspects of children's experiences with digital media. Recommendations for further research are to conduct more in-depth empirical studies and develop intervention strategies that engage parents, educators, and policymakers to create a more supportive and inclusive digital environment for children's gender identity development.